Aircraft study of the impact of lake-breeze circulations on trace gases and particles during BAQS-Met 2007 - Hayden, K. L.; Sills, D. M. L.; Brook, J. R.; Li, S. -M.; Makar, P. A.; Markovic, M. Z.; P Liu; Anlauf, K. G.; O'Brien, J. M.; Li, Q.; McLaren, R. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2011)
High time-resolved aircraft data, concurrent surface measurements and air quality model simulations were explored to diagnose the processes influencing aerosol chemistry under the influence of lake-breeze circulations in a polluted region of southwestern Ontario, Canada. The analysis was based upon horizontal aircraft transects conducted at multiple altitudes across an entire lake-breeze circulation. Air mass boundaries due to lake-breeze fronts were identified in the aircraft meteorological and chemical data, which were consistent with the frontal locations determined from surface analyses. Observations and modelling support the interpretation of a lake-breeze circulation where pollutants were lofted at a lake-breeze front, transported in the synoptic flow, caught in a downdraft over the lake, and then confined by onshore flow. The detailed analysis led to the development of conceptual models that summarize the complex 3-D circulation patterns and their interaction with the synoptic flow. The identified air mass boundaries, the interpretation of the lake-breeze circulation, and the air parcel circulation time in the lake-breeze circulation (3.0 to 5.0 h) enabled formation rates of organic aerosol (OA/Delta CO) and SO42- to be determined. The formation rate for OA (relative to excess CO in ppmv) was found to be 11.6-19.4 mu g m(-3) ppmv(-1) h(-1) and the SO42- formation rate was 5.0-8.8 % h(-1). The formation rates are enhanced relative to regional background rates implying that lake-breeze circulations are an important dynamic in the formation of SO42- and secondary organic aerosol. The presence of cumulus clouds associated with the lake-breeze fronts suggests that these enhancements could be due to cloud processes. Additionally, the effective confinement of pollutants along the shoreline may have limited pollutant dilution leading to elevated oxidant concentrations.